Measuring the cointegration of housing types in Northern Ireland. Issue 4 (2nd October 2019) - McCord, Michael; Lo, Daniel; McCord, John; Davis, Peadar Thomas; Haran, Martin
ABSTRACT: The primary purpose of this paper is to examine the dynamic and Granger causal (inter) relationships between house prices and to empirically assess the co-movement in-house prices across different property types within Northern Ireland (NI). The Johansen cointegration, Granger causality tests and vector error correction model are applied to quarterly house price data for the NI housing market between Q1 1995 and Q2 2018 to determine whether price transmissions are propagated contemporaneously into both short-term and long-term price adjustments. The findings show the stylised facts of lead–lag relationships across property types in NI using long-term Granger causality tests that the performance of the Apartment sector systematically and consistently lagged behind all other residential property segments over the period. Indeed, the results indicate that there are obvious market filtration transmission pricing signals in operation in a Granger-causal fashion. Property price signals are observed to be transmitted from the more liquid owner-occupier-led Detached and Semi-detached segments to the Apartment segment, but not vice versa.